S100A8/A9 as a risk factor for breast cancer negatively regulated by DACH1 - Xiaojun Zhang; Mengke Niu; Tianye Li; Yuze Wu; Jinnan Gao; Ming Yi; Kongming Wu (BMC, 2023)
Abstract Background S100A8 and S100A9 are members of Ca2+-binding EF-hand superfamily, mainly expressed by macrophages and neutrophils. Limited by the poor stability of homodimers, they commonly exist as heterodimers. Beyond acting as antibacterial cytokines, S100A8/A9 is also associated with metabolic and autoimmune diseases such as obesity, diabetes, and rheumatoid arthritis. While the involvement of S100A8/A9 in breast cancer development has been documented, its prognostic significance and the precise regulatory mechanisms remain unclear. Methods S100A8/A9 protein in breast cancer samples was evaluated by immunohistochemistry staining with tumor tissue microarrays. The serum S100A8 concentration in patients was measured by enzyme-linked immunosorbent assay (ELISA). The S100A8 secreted by breast cancer cells was detected by ELISA as well. Pooled analyses were conducted to explore the relationships between S100A8/A9 mRNA level and clinicopathological features of breast cancer patients. Besides, the effects of S100A8/A9 and DACH1 on patient outcomes were analyzed by tissue assays. Finally, xenograft tumor assays were adopted to validate the effects of DACH1 on tumor growth and S100A8/A9 expression. Results The level of S100A8/A9 was higher in breast cancer, relative to normal tissue. Increased S100A8/A9 was related to poor differentiation grade, loss of hormone receptors, and Her2 positive. Moreover, elevated S100A8/A9 predicted a worse prognosis for breast cancer patients. Meanwhile, serum S100A8 concentration was upregulated in Grade 3, basal-like, and Her2-overexpressed subtypes. Additionally, the results of public databases showed S100A8/A9 mRNA level was negatively correlated to DACH1. Stable overexpressing DACH1 in breast cancer cells significantly decreased the generation of S100A8. The survival analysis demonstrated that patients with high S100A8/A9 and low DACH1 achieved the shortest overall survival. The xenograft models indicated that DACH1 expression significantly retarded tumor growth and downregulated S100A8/A9 protein abundance. Conclusion S100A8/A9 is remarkedly increased in basal-like and Her2-overexpressed subtypes, predicting poor prognosis of breast cancer patients. Tumor suppressor DACH1 inhibits S100A8/A9 expression. The combination of S100A8/A9 and DACH1 predicted the overall survival of breast cancer patients more preciously.